FAKTOR-FAKTOR PENDORONG INDONESIA MENYETUJUI PERJANJIAN EKONOMI DENGAN AUSTRALIA DALAM INDONESIA-AUSTRALIA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IA-CEPA) - Julianisa, Kadek Dwisia; Priadarsini, Ni Wayan Rainy; Sushanti, Sukma (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
Indonesia agreed to increase bilateral economic cooperation with Australia in the Indonesia Australia-Comprehensive Economic Partnership Agreement (IA-CEPA). The results of the IA-CEPA agreement discuss trade, services, investment, E-commerce, competition policy, economic cooperation, institutional provisions, and frameworks. However, based on the IA-CEPA agreement, it poses many threats to Indonesia in the fields of exports, imports, and investment. Australia is one of the countries that contributes to the largest trade deficit to Indonesia. In the investment sector, the amount of investment entering Indonesia has not been well controlled by Indonesia, thus deepening Indonesia’s balance of payments deficit. This study uses a descriptive qualitative method with the concept of determinant factors on foreign policy by William D. Coplin. It was found that there are factors that influence Indonesia’s decision to approve the IA-CEPA, namely domestic politic conditions, economic and military conditions and international contexts.